Do home computers improve educational outcomes? Evidence from matched current population surveys and the national longitudinal survey of youth 1997 - Daniel O. Beltran; Kuntal K. Das; Robert W. Fairlie (Institute for the Study of Labor (IZA), 2006)
Nearly twenty million children in the United States do not have computers in their homes. The role of home computers in the educational process, however, has drawn very little attention in the previous literature. We use panel data from the two main U.S. datasets that include recent information on computer ownership among children - the 2000-2003 CPS Computer and Internet Use Supplements (CIUS) matched to the CPS Basic Monthly Files and the National Longitudinal Survey of Youth 1997 - to explore the relationship between computer ownership and high school graduation and other educational outcomes. Teenagers who have access to home computers are 6 to 8 percentage points more likely to graduate from high school than teenagers who do not have home computers after controlling for individual, parental, and family characteristics. We generally find evidence of positive relationships between home computers and educational outcomes using several estimation strategies, including controlling for typically unobservable home environment and extracurricular activities in the NLSY97, fixed effects models, instrumental variables, future computer ownership and pencil tests. Some of these estimation techniques, however, provide imprecise estimates. Home computers may increase high school graduation by reducing non-productive activities, such as truancy and crime, among children in addition to making it easier to complete school assignments.
Keywords: I2; 330; computers; educational outcomes; technology